Enhanced translation expands the endo-lysosome size and promotes antigen presentation during phagocyte activation. - Victoria E B Hipolito; Jacqueline A Diaz; Kristofferson V Tandoc; Christian Oertlin; Johannes Ristau; Neha Chauhan; Amra Saric; Shannon Mclaughlan; Ola Larsson; Ivan Topisirovic; Roberto J Botelho (PLoS Biology)
The mechanisms that govern organelle adaptation and remodelling remain poorly defined. The endo-lysosomal system degrades cargo from various routes, including endocytosis, phagocytosis, and autophagy. For phagocytes, endosomes and lysosomes (endo-lysosomes) are kingpin organelles because they are essential to kill pathogens and process and present antigens. During phagocyte activation, endo-lysosomes undergo a morphological transformation, going from a collection of dozens of globular structures to a tubular network in a process that requires the phosphatidylinositol-3-kinase-AKT-mechanistic target of rapamycin (mTOR) signalling pathway. Here, we show that the endo-lysosomal system undergoes an expansion in volume and holding capacity during phagocyte activation within 2 h of lipopolysaccharides (LPS) stimulation. Endo-lysosomal expansion was paralleled by an increase in lysosomal protein levels, but this was unexpectedly largely independent of the transcription factor EB (TFEB) and transcription factor E3 (TFE3), which are known to scale up lysosome biogenesis. Instead, we demonstrate a hitherto unappreciated mechanism of acute organelle expansion via mTOR Complex 1 (mTORC1)-dependent increase in translation, which appears to be mediated by both S6Ks and 4E-BPs. Moreover, we show that stimulation of RAW 264.7 macrophage cell line with LPS alters translation of a subset but not all of mRNAs encoding endo-lysosomal proteins, thereby suggesting that endo-lysosome expansion is accompanied by functional remodelling. Importantly, mTORC1-dependent increase in translation activity was necessary for efficient and rapid antigen presentation by dendritic cells. Collectively, we identified a previously unknown and functionally relevant mechanism for endo-lysosome expansion that relies on mTORC1-dependent translation to stimulate endo-lysosome biogenesis in response to an infection signal.